2021
DOI: 10.46328/ijemst.1157
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gamified STEM Practices on Students’ Intrinsic Motivation, Critical Thinking Disposition Levels, and Perception of Problem-Solving Skills

Abstract: The aim of this research is to examine the effect of gamified STEM activities on 3rd and 4th grade students’ intrinsic motivation, perception of problem-solving skills, and critical thinking disposition. In this mixed method study, problem solving skills perception scale, critical thinking disposition instrument and intrinsic motivation inventory formed the quantitative data, while, activity worksheets, field notes and student interviews, formed the qualitative data. After 8 weeks of implementation, quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 0 publications
5
29
0
1
Order By: Relevance
“…science, and other teachers while conducting STEM-based activities. Many studies in the literature reached similar conclusions(Akaygun & Aslan-Tutak;Asigigan & Samur, 2021;Aslan-Tutak et al, 2017;Aslan & Bektas, 2019;Li et al, 2020;Margot & Kettler, 2019;Ozbilen, 2018;Yildirim, 2016). The studies have shown that STEM education is important for teachers' own fields.The findings of the study show that STEM education has positive effects on both students' 21st century skills and Gok 554 teachers' professional development.Appendix.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…science, and other teachers while conducting STEM-based activities. Many studies in the literature reached similar conclusions(Akaygun & Aslan-Tutak;Asigigan & Samur, 2021;Aslan-Tutak et al, 2017;Aslan & Bektas, 2019;Li et al, 2020;Margot & Kettler, 2019;Ozbilen, 2018;Yildirim, 2016). The studies have shown that STEM education is important for teachers' own fields.The findings of the study show that STEM education has positive effects on both students' 21st century skills and Gok 554 teachers' professional development.Appendix.…”
mentioning
confidence: 66%
“…Difficulties in implementing STEM education (Leung, 2020), teachers' experiences in STEM education (Aslan-Tutak, Akaygun, & Tezsezen, 2017;Brown & Bogiages, 2019;Eroglu & Bektas, 2016;Shernoff et al, 2017), studies on curriculum development for STEM education (Aslan-Tutak et al, 2017;Ntemngwa & Oliver, 2018), perceptions and motivations of teachers for STEM education (Akaygun & Aslan-Tutak, 2016;Haciomeroglu, 2018;Karisan, Macalalag, & Johnson, 2019;Kim & Bolger, 2017;Landicho, 2020;Margot & Kettler, 2019;Nguyen, Nguyen, & Tran, 2020), qualitative studies conducted on STEM education (Wilson, Campbell-Gulley, Anthony, Peréz, & England, 2022), the importance of technology use strategies and alternative teaching models to support the learning of the students on the STEM education (Asigigan & Samur, 2021;Wu, Cheng, & Koszalka, 2021;Yang & Baldwin, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The participants disclosed the notion that the use of game-based activities in teaching physical education helped them transform into students with sufficient skills in the classroom such as collaboration, creativity, problem-solving, logic, and analytical thinking, which pushes them to think critically and smartly. As evidently supported by Asigigan and Samur (2021), game-based activities positively and significantly influenced students' problemsolving skills such as analysis, synthesis, and evaluation. Subsequently, Smiderle et al (2020) discovered that the gamified system changed students' behavior, resulting in a significant improvement in the quality of their submitted solutions and greater accuracy of the answers submitted, indicating that when In a world shattered by the COVID-19 pandemic, the development of gamified teaching strategies may appear to be a promising option for imparting knowledge and increasing student engagement.…”
Section: Influence Of Gamified Instruction On Students' Engagement Th...mentioning
confidence: 79%
“…Gamification is primarily described as the usage of game elements in a non-game context ( Deterding, 2012 ) and can be described from the behavioral perspective ( Morford et al., 2014 ). The main goal of gamification is to change the usage habits or behaviors of the individual ( Asigigan and Samur, 2021 ). Implementing gamification as an instructional tool in classrooms is effective not only to make students part of activities but also to motivate them at the same time ( Muntean, 2011 ).…”
Section: Introductionmentioning
confidence: 99%